Effects of cascade reservoirs on the transformation of nitrogen in pore water of sediments in the Lancang River. (3rd February 2021) - Zhao, Ping; Wang, Congfeng; Wang, Xue; Yang, Zhengjian; Liu, Defu
Abstract: In the mainstream of the Lancang River, eight cascade dams have been constructed. In order to find the effects of the cascade reservoirs on the transformation of nitrate (NO3 ‐N) and ammonium (NH4 ‐N) in pore water of sediments, a field survey was carried out both in the upper natural river reach (NRR) and cascade reservoirs reach (CRR) of the Lancang River from January 10 to 20, 2018. The results indicated that (1) in the NRR, NO3 ‐N concentrations in sediment pore water were higher than those in the CRR, whereas the total nitrogen (TN) and NH4 ‐N were significantly lower; the diffusion fluxes of NH4 ‐N from sediment to overlying water varied from −0.180 to 0.049 mg·(m 2 ·d) ‐1, and the diffusion fluxes of NO3 ‐N varied from 0.012 to 0.098 mg·(m 2 ·d) ‐1 . (2) in the CRR, the NH4 ‐N concentrations in sediment pore water were much higher than those in the overlying water, but the NO3 ‐N concentrations in the overlying water were much higher; the diffusion fluxes of NH4 ‐N from the sediments to the overlying water varied from 0.161 to 1.561 mg·(m 2 ·d) ‐1, but the NO3 ‐N diffused downward from the overlying water to the sediments and the diffusion fluxes varied from −0.011 to −0.223 mg·(m 2 ·d) ‐1 . It was concluded that the cascade reservoirs could increase the NH4 ‐N concentration and inversely decrease the NO3 ‐N concentration in the sediment pore water, which meant that the risk of the nitrogen release from the sediment in the cascade reservoirs was much higher than that in the natural river.